All-optical switching in subwavelength metallic grating structure containing nonlinear optical materials - Min, Changjun; Wang, Pei; Chen, Chunchong; Deng, Yan; Lu, Yonghua; Ming, Hai; Ning, Tingyin; Zhou, Yueliang; Yang, Guozhen (Optics letters, 2008)
All-optical switching based on a subwavelength metallic grating structure containing nonlinear optical materials has been proposed and numerically investigated. Metal-dielectric composite material is used in the switching for its larger third-order nonlinear susceptibility (approximately 10(-7)esu) and ultrafast response properties. The calculated dependence of the signal light intensity on the pump light intensity shows a bistable behavior, which results in a significant switch effect. It rests on a surface plasmon's enhanced intensity-dependent change of the effective dielectric constant of Kerr nonlinear media, corresponding to a transition of the far-field transmission from a low- to high-transmission state. The study of this switching structure shows great advantages of smaller size, lower requirement of pump light intensity, and shorter switching time at approximately the picosecond level.